(untitled) (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This research and development was motivated by the low learning outcomes of fifth-grade students at SDN 1 Bagorkulon in the science subject, particularly on the terrestrial ecosystem material. This problem was caused by conventional teaching methods and the lack of engaging media utilization. This study aimed to develop and determine the validity, practicality, and effectiveness of the EKSIDA (Ekosistem Darat) interactive learning media to improve student learning outcomes. This study employed the Research and Development method with the 4-D (Define, Design, Develop, Disseminate) development model. The research subjects were the fifth-grade students of SDN 1 Bagorkulon. Data collection instruments included validation questionnaires, student response questionnaires, and pre-test/post-test questions. The results showed that the EKSIDA media was declared "very valid" with percentage scores of 90% from the material expert, 93% from the media expert, and 89% from the practitioner (teacher). The media’s practicality was categorized as "very good" based on student responses, with scores of 98% in the limited trial and 90% in the broad trial. The media’s effectiveness was proven to significantly improve student learning outcomes, as evidenced by N-gain scores of 0.77 (limited trial) and 0.71 (broad trial), both of which are in the "high" category. Therefore, the EKSIDA interactive learning media is valid, practical, and effective to be used in the learning process.